THU0470 Association of Relapsing Polychondritis with Other Autoimmune Conditions: Experience of a Romanian Center. (23rd January 2014) - Ghib, L. J.; Damian, L.; Andrei, M.; Felea, I.; Simon, S.-P.; Bojan, A.; Maniu, A.; Rednic, S.
Abstract : Background: Relapsing polychondritis(RP) is a rare inflammatory disease affecting cartilaginous structures. About one third of the patients with RP have a concurrent or preceding autoimmune disease thus making diagnosis difficult. Objectives: To assess the types and prevalence of autoimmune diseases associated with RP patients diagnosed in a single Rheumatology tertiary center. Methods: Retrospective analysis of all patients diagnosed with RP over a 12-year period (2000 to 2012) was employed using the hospital and outpatient databases. Diagnosis of RP was made using the McAdam criteria and autoimmune associated diseases (AAD) were defined in accordance with standard international criteria. Results: We diagnosed 34 patients (76.4% women) with RP. Mean age at diagnosis was 44.5 ± 16.9 years with a time from onset of 36 months (1-168), after consultations of 4 other specialists (1-8). 22(64%) of our patients had one or more AAD: 10 vasculitis: 2 Behcet/MAGIC, 3 Microscopic Polyangiitis, 1 Wegener granulomatosis, 1 AGC, 1 Undifferentiated vasculitis, 2 Cerebral vasculitis. Five patients had Systemic Lupus Erytematosus, 3 Sjogren syndrome, 1 dermatomyositis, 2 psoriatic arthritis, 1 Hashimoto thyroiditis, 1 Still disease and one rheumatoid arthritis. Interestingly 7 of the patients without AAD had hemathological abnormalities- malignancies were noted in 3 patients, 2 of them diagnosed after RP onset, Common variable immunodeficiency in one patient and Hemophagocytic Syndrome in another. Mean age at diagnosis was 43 for patients with AAD and 46 for non-AAD patients, with a longer time from onset to diagnosis for the non AAD patients (4.44 vs 3.45, p=NS). Cartilage involvement was similar between the two groups. A higher frequency of eye involvement was noted in the non AAD group: scleritis (25% vs 0%, p=0.01), episcleritis (50% vs 4.8%, p=0.03) and loss of vision (16.7% vs 4.8%, p=NS). No significant differences were noted between the two groups regarding cardiovascular, ENT, articular or neurological involvement. Glomerulonephritis had a higher prevalence in the AAD group (9 vs 3), but the difference was not statistically significant. As expected, AAN (57.1% vs 23.1%, p=0.02) and low complement (C3: 23.8% vs 7.7%, p=NS, C4: 15.4% vs 28.6%) were more frequent in the AAD group. Renal (20% vs ), cardiovascular(25% vs 7.7%) and respiratory(35% vs 15.4%) damage were higher in the AAD group, but no statistical difference was noted. Conclusions: In our sample AAD were more frequent then reported in the literature, possibly due to referral bias. RP with AAD seems to have poorer outcome with higher organ damage. Awareness of the association of non AAD RP with haematologycal disturbances should prompt the physician for a more detailed screening in this direction. References: McAdam LP, O'Hanlan MA, Bluestone R, Pearson CM. Relapsing polychondritis: prospective study of 23 patients and a review of the literature. Medicine (Baltimore) . May 1976;55(3):193-215. Cohen PR: Paraneoplastic relapsing polychondritis. Arch Dermatol 2007; 143(7): 949-50. Letko E, Zafirakis P, Baltatzis S, Voudouri A, Livir-Rallatos C, Foster CS. Relapsing polychondritis: a clinical review. Semin Arthritis Rheum . Jun 2002;31(6):384-95. Disclosure of Interest: None Declared